Mechanical properties of plasma polymer films controlled by RF power - Palesch, Erik; Kontarova, Sona; Cech, Vladimir (International Conference on Plasma Surface Engineering, 2013)
This study deals with plasma polymer films deposited on silicon substrates using tetravinylsilane monomer. The deposition technique was plasma-enhanced chemical vapour deposition. Nanoindentation was used as a method to investigate mechanical properties of samples prepared at different RF powers. The Young’s modulus and hardness of thin films were estimated from load-displacement curves. The nanoscratch test was employed to determine the critical normal load needed for film delamination, as a parameter describing adhesion to the substrate. AFM images of scratches were carried out to correlate the data with nature and shape of scratches.